Paul's Online Notes
Paul's Online Notes
Home / Calculus I / Derivatives / Chain Rule
Show Mobile Notice Show All Notes Hide All Notes
Mobile Notice
You appear to be on a device with a "narrow" screen width (i.e. you are probably on a mobile phone). Due to the nature of the mathematics on this site it is best views in landscape mode. If your device is not in landscape mode many of the equations will run off the side of your device (should be able to scroll to see them) and some of the menu items will be cut off due to the narrow screen width.
Assignment Problems Notice
Please do not email me to get solutions and/or answers to these problems. I will not give them out under any circumstances nor will I respond to any requests to do so. The intent of these problems is for instructors to use them for assignments and having solutions/answers easily available defeats that purpose.

Section 3-9 : Chain Rule

For problems 1 – 51 differentiate the given function.

  1. \(g\left( x \right) = {\left( {3 - 8x} \right)^{11}}\)
  2. \(g\left( z \right) = \sqrt[7]{{9{z^3}}}\)
  3. \(h\left( t \right) = {\left( {9 + 2t - {t^3}} \right)^6}\)
  4. \(y = \sqrt {{w^3} + 8{w^2}} \)
  5. \(R\left( v \right) = {\left( {14{v^2} - 3v} \right)^{ - 2}}\)
  6. \(\displaystyle H\left( w \right) = \frac{2}{{{{\left( {6 - 5w} \right)}^8}}}\)
  7. \(f\left( x \right) = \sin \left( {4x + 7{x^4}} \right)\)
  8. \(T\left( x \right) = \tan \left( {1 - 2{{\bf{e}}^x}} \right)\)
  9. \(g\left( z \right) = \cos \left( {\sin \left( z \right) + {z^2}} \right)\)
  10. \(h\left( u \right) = \sec \left( {{u^2} - u} \right)\)
  11. \(y = \cot \left( {1 + \cot \left( x \right)} \right)\)
  12. \(f\left( t \right) = {{\bf{e}}^{1 - {t^{\,2}}}}\)
  13. \(J\left( z \right) = {{\bf{e}}^{12z - {z^{\,6}}}}\)
  14. \(f\left( z \right) = {{\bf{e}}^{z + \ln \left( z \right)}}\)
  15. \(B\left( x \right) = {7^{\cos \left( x \right)}}\)
  16. \(z = {3^{{x^{\,2}} - 9x}}\)
  17. \(R\left( z \right) = \ln \left( {6z + {{\bf{e}}^z}} \right)\)
  18. \(h\left( w \right) = \ln \left( {{w^7} - {w^5} + {w^3} - w} \right)\)
  19. \(g\left( t \right) = \ln \left( {1 - \csc \left( t \right)} \right)\)
  20. \(f\left( v \right) = {\tan ^{ - 1}}\left( {3 - 2v} \right)\)
  21. \(h\left( t \right) = {\sin ^{ - 1}}\left( {9t} \right)\)
  22. \(A\left( t \right) = \cos \left( t \right) - \sqrt[6]{{1 - \sin \left( t \right)}}\)
  23. \(H\left( z \right) = \ln \left( {6z} \right) - 4\sec \left( z \right)\)
  24. \(f\left( x \right) = {\tan ^4}\left( x \right) + \tan \left( {{x^4}} \right)\)
  25. \(f\left( u \right) = {{\bf{e}}^{4u}} - 6{{\bf{e}}^{ - u}} + 7{{\bf{e}}^{{u^{\,2}} - 8u}}\)
  26. \(g\left( z \right) = {\sec ^8}\left( z \right) + \sec \left( {{z^8}} \right)\)
  27. \(k\left( w \right) = {\left( {{w^4} - 1} \right)^5} + \sqrt {2 + 9w} \)
  28. \(h\left( x \right) = \sqrt[3]{{{x^2} - 5x + 1}} + {\left( {9x + 4} \right)^{ - 7}}\)
  29. \(T\left( x \right) = {\left( {2{x^3} - 1} \right)^5}{\left( {5 - 3x} \right)^4}\)
  30. \(w = \left( {{z^2} + 4z} \right)\sin \left( {1 - 2z} \right)\)
  31. \(Y\left( t \right) = {t^8}{\cos ^4}\left( t \right)\)
  32. \(f\left( x \right) = \sqrt {6 - {x^4}} \,\,\,\ln \left( {10x + 3} \right)\)
  33. \(A\left( z \right) = \sec \left( {4z} \right)\tan \left( {{z^2}} \right)\)
  34. \(h\left( v \right) = \sqrt {5v} + \ln \left( {{v^4}} \right){{\bf{e}}^{6 + 9v}}\)
  35. \(\displaystyle f\left( x \right) = \frac{{{{\bf{e}}^{{x^{\,2}} + 8x}}}}{{\sqrt {{x^4} + 7} }}\)
  36. \(\displaystyle g\left( x \right) = \frac{{{{\left( {4x + 1} \right)}^3}}}{{{{\left( {{x^2} - x} \right)}^6}}}\)
  37. \(\displaystyle g\left( t \right) = \frac{{\csc \left( {1 - t} \right)}}{{1 + {{\bf{e}}^{ - t}}}}\)
  38. \(\displaystyle V\left( z \right) = \frac{{{{\sin }^2}\left( z \right)}}{{1 + \cos \left( {{z^2}} \right)}}\)
  39. \(U\left( w \right) = \ln \left( {{{\bf{e}}^w}\cos \left( w \right)} \right)\)
  40. \(h\left( t \right) = \tan \left( {\left( {5 - {t^2}} \right)\ln \left( t \right)} \right)\)
  41. \(\displaystyle z = \ln \left( {\frac{{3 + x}}{{2 - {x^2}}}} \right)\)
  42. \(\displaystyle g\left( v \right) = \sqrt {\frac{{{{\bf{e}}^v}}}{{7 + 2v}}} \)
  43. \(f\left( x \right) = \sqrt {{x^2} + \sqrt {1 + 4x} } \)
  44. \(u = {\left( {6 + \cos \left( {8w} \right)} \right)^5}\)
  45. \(h\left( z \right) = {\left( {7z - {z^2} + {{\bf{e}}^{5{z^{\,2}} + z}}} \right)^{ - 4}}\)
  46. \(A\left( y \right) = \ln \left( {7{y^3} + {{\sin }^2}\left( y \right)} \right)\)
  47. \(g\left( x \right) = {\csc ^6}\left( {8x} \right)\)
  48. \(V\left( w \right) = \sqrt[4]{{\cos \left( {9 - {w^2}} \right) + \ln \left( {6w + 5} \right)}}\)
  49. \(h\left( t \right) = \sin \left( {{t^3}{{\bf{e}}^{ - 6t}}} \right)\)
  50. \(B\left( r \right) = {\left( {{{\bf{e}}^{\sin \left( r \right)}} - \sin \left( {{{\bf{e}}^r}} \right)} \right)^8}\)
  51. \(f\left( z \right) = {\cos ^2}\left( {1 + {{\cos }^2}\left( z \right)} \right)\)
  52. Find the tangent line to \(f\left( x \right) = {\left( {2 - 4{x^2}} \right)^5}\) at \(x = 1\).
  53. Find the tangent line to \(f\left( x \right) = {{\bf{e}}^{2x + 4}} - 8\ln \left( {{x^2} - 3} \right)\) at \(x = - 2\).
  54. Determine where \(A\left( t \right) = {t^3}{\left( {9 - t} \right)^4}\) is increasing and decreasing.
  55. Is \(h\left( x \right) = {\left( {2x + 1} \right)^4}{\left( {2 - x} \right)^5}\) increasing or decreasing more in the interval \(\left[ { - 2,3} \right]\)?
  56. Determine where \(\displaystyle U\left( w \right) = 3\cos \left( {\frac{w}{2}} \right) + w - 3\) is increasing and decreasing in the interval \(\left[ { - 10,10} \right]\).
  57. If the position of an object is given by \(s\left( t \right) = 4\sin \left( {3t} \right) - 10t + 7\). Determine where, if anywhere, the object is not moving in the interval \(\left[ {0,4} \right]\).
  58. Determine where \(f\left( x \right) = 6\sin \left( {2x} \right) - 7\cos \left( {2x} \right) - 3\) is increasing and decreasing in the interval \(\left[ { - 3,2} \right]\).
  59. Determine where \(H\left( w \right) = \left( {{w^2} - 1} \right){{\bf{e}}^{2 - {w^{\,2}}}}\) is increasing and decreasing.
  60. What percentage of \(\left[ { - 3,5} \right]\) is the function \(g\left( z \right) = {{\bf{e}}^{{z^2} - 8}} + 3{{\bf{e}}^{1 - 2{z^2}}}\) decreasing?
  61. The position of an object is given by \(s\left( t \right) = \ln \left( {2{t^3} - 21{t^2} + 36t + 200} \right)\). During the first 10 hours of motion (assuming the motion starts at \(t = 0\)) what percentage of the time is the object moving to the right?
  62. For the function \(\displaystyle f\left( x \right) = 1 - \frac{x}{2} - \ln \left( {2 + 9x - {x^2}} \right)\) determine each of the following.
    1. The interval on which the function is defined.
    2. Where the function is increasing and decreasing.